High-Level Expression of Immunogenic Recombinant Plasmodium vivax Merozoite Surface Protein (Pvmsp-1(42) kDa) in pGEX 6P1 Vector - MIRAHMADI, Hadi (Iran J Public Health, 2015)
BACKGROUND: Detection of Plasmodium vivax specific antibodies with serological tests could be a valuable tool for epidemiological researches. Whereas P. vivax cannot be simply obtained in vitro, serological tests using total or semi-purified antigens are infrequently used. Given this restriction, the present study investigated whether recombinant P. vivax merozoite surface protein 1 (PvMSP-1 (42) kDa) could be useful in detection of antibodies from the serums of a P. vivax infected person using serological tests. METHODS: Parasite DNA was extracted from blood sample of an Iranian P. vivax-infected patient. The region of PvMSP-1(42) kDa was amplified by PCR then cloned into pTZ57R/T vector and sequenced. The insert was sub cloned into pGEX 6P1 expression vector. Afterwards, it was transformed into E. coli BL21 and cultured massively. Sub cloning of gene was confirmed by PCR and enzyme digestion and sequencing finally. Production of recombinant protein was confirmed by SDS-PAGE. Western blot was performed by human sera to appraisal binding ability to the IgG antibodies of P. vivax infected patients. Recombinant protein was purified and estimated by Bradford assay. RESULTS: The specialty values of the Western blot determined with 10 sera from naturally infected individuals, 10 sera from healthy individuals and 7 sera from individuals with other infectious diseases. CONCLUSION: For the Iranian population, using a Western blot assay for MSP-1(42) recombinant protein can be used as the foundation for promotion of serological assay for the detection of P. vivax malaria such as ELISA.